(untitled) (International Journal of Environmental Sciences, 2025)
Studying gender equality and unpaid work is important because it exposes the systemic undervaluation of women’s contributions to the economy and society. Unpaid work, such as caregiving, housework, and subsistence activities, is primarily done by women and is largely considered worthless and unaccounted for in other traditional measures such as GDP. The intention of this article is to provide an overview and summary of the research on the concept and practices of gender equality and unpaid work. To do so, this study uses bibliometric analysis to examine the trends and characteristics of scholarly publications from 1991 to 2023 across a dataset comprising 2,489 journal articles sourced from 911 academic outlets.The article reports on the publication and its citation structure, key trends, and its growing push toward co-authoring. This study also visualises the most prominent topics and authors in the form of a network, using VOSviewer’s bibliometric analysis. The study reveals a robust annual growth rate of 18.2%, indicating a rising interest in the research domain. The entire dataset consists of peer-reviewed journal articles, reflecting the academic rigour and dissemination of the research field. This analysis offers valuable insights into scholarly communication’s evolution, collabouration patterns, and impact over the three-decade period.